2009
DOI: 10.1098/rspb.2009.0004
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in distance perception

Abstract: Distance perception is among the most pervasive mental phenomena and the oldest research topics in behavioural science. However, we do not understand well the most pervasive finding of distance perception research, that of large individual differences. There are large individual differences in acrophobia (fear of heights), which we commonly assume consists of an abnormal fear of stimuli perceived normally. Evolved navigation theory (ENT) instead suggests that acrophobia consists of a more normal fear of stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 29 publications
(31 reference statements)
4
31
0
Order By: Relevance
“…Data from a repeated-measures analysis of variance suggested significant differences between edge and ground estimates, F(1, 52) = 57.98, p < .001, a significant difference in magnitude across stimulus lengths, F(2, 104) = 15.58, p = .004, and no significant interaction between these two variables, F(2, 104) = 0.07, p = .934. This manipulation generally replicated the results of similar manipulations in previous research (Jackson, 2005(Jackson, , 2009Jackson & Cormack, 2007, 2008Jackson & Willey, 2011).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Data from a repeated-measures analysis of variance suggested significant differences between edge and ground estimates, F(1, 52) = 57.98, p < .001, a significant difference in magnitude across stimulus lengths, F(2, 104) = 15.58, p = .004, and no significant interaction between these two variables, F(2, 104) = 0.07, p = .934. This manipulation generally replicated the results of similar manipulations in previous research (Jackson, 2005(Jackson, , 2009Jackson & Cormack, 2007, 2008Jackson & Willey, 2011).…”
Section: Resultssupporting
confidence: 88%
“…ground). Underestimation in order to increase safe navigation extends directly from the ENT concept of overestimation in order to decrease risky navigation outlined in previous literature (Jackson, 2005(Jackson, , 2009(Jackson, , 2013Jackson & Cormack, 2006, 2007, 2008Jackson & Willey, 2011). Although the visual setting of Experiment 1 did not generate a clear underestimation, we observed the expected underestimation across all expected distances in Experiment 2, plausibly generated by the presence of clear navigation risks.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…It has been found that those factors result in significant overestimation of geographical slant (Stefanucci et al 2008) or height (Jackson 2009;Stefanucci and Storbeck 2009). In the study of Stefanucci et al (2008), the subjects were asked to estimate the slant of the hill slope while standing on either a skateboard or a wooden box of the same height.…”
Section: State Estimation Bias Reflected As Safety Marginmentioning
confidence: 96%